A cross sectional study on defective vision among secondary school going children in Vijayawada city, Andhra Pradesh - Durga Kumar, Chinta; Anga, Venkata Suresh (International Journal Of Community Medicine And Public Health, 2018)
Background: Eye is one of the most vital organs of human body. Any abnormality in the eye can impair vision and make the person handicapped for life. The school children form a special group because they are most vulnerable to the effects of reduced vision and its impact on learning capability and educational potential. The objective of the study was to find out the factors affecting vision of secondary school children, to suggest preventive and remedial measures for defective vision. Methods: It was a cross sectional study. School children of Zilla Parishad secondary high school during November 2016 to December 2016 were studied. A pretested semi structured questionnaire was administered. A total of 320 students were included in the study by using convenient sampling technique. Data was entered in Microsoft excel sheet and analyzed using Statistical Package for Social Sciences (SPSS) version 20. Results were expressed as proportions for different study variables. Results: Out of the 320 students, majority 181 (56.56%) of study participants were girls. The highest number of students (49.38%) was between 12-13 years of age group. Prevalence of defective vision is 34%. Family history is present in 29% of the study population. 34% of children with defective vision, it was detected by their mother. Conclusions: Refractive errors are more in girls. Children and parents should be educated regarding ocular hygiene and early correction of refractive errors.